2013
DOI: 10.1002/jhet.1522
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of 3‐(Substituted arylmethyl)‐4‐acylaminomethyloxazolidin‐2‐ones and Derivatization to Symmetrical Twin‐Drug Type Molecules

Abstract: In connection with our studies on antibacterial active compounds in the class of new oxazolidinones against Gram‐positive (Staphylococcus aureus) and Gram‐negative (Escherichia coli) strains, some molecular modifications were attempted. In this study, molecular modifications of 4‐aminomethyloxazolidin‐2‐ones (3a) to the corresponding 4‐acylaminomethyloxazolidin‐2‐one derivatives (3c–d) and preparations of the represented twin‐drug type molecules (10–14) were investigated. Some additional 4‐dialkylaminomethylox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The results are summarized in Tables 1 and 2. It is thought that the tautomeric isomer B of 5-methylene hydantoin in solution (A B) 17,19) is a crucial intermediate for the formation of 5,5-disubstituted hydantoins (11)(12)(13)(14), as shown in Chart 2. When using an excess amount of an amine, a considerable amount of ring-opened urea derivatives 15-17 was isolated as a predominant reaction product (Chart 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are summarized in Tables 1 and 2. It is thought that the tautomeric isomer B of 5-methylene hydantoin in solution (A B) 17,19) is a crucial intermediate for the formation of 5,5-disubstituted hydantoins (11)(12)(13)(14), as shown in Chart 2. When using an excess amount of an amine, a considerable amount of ring-opened urea derivatives 15-17 was isolated as a predominant reaction product (Chart 2).…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] From this interesting aspect of molecular symmetry, we have already reported a few examples of such types of symmetrical targeted molecules for the purpose of finding new bioactive leads or candidates. [10][11][12][13][14][15] Our previous studies on a bioisosteric replacement of the oxazolidinone ring in linezolid by a hydantoin nucleus provided a few interesting antibacterial leads. [16][17][18][19][20] Among previously targeted hydantoin derivatives, some derivatives including a twin-drug type symmetrical hydantoin derivative 20,21) showed significant antibacterial activity against Gram-positive organisms (Staphylococcus aureus).…”
mentioning
confidence: 99%
“…Fujisaki et al report the synthesis of novel oxazolidinone dimers that showed significant activity against both Gram-negative and Gram-positive bacteria [84].…”
Section: Fig 34 Azithromycin (A) and Erythromycin (B)mentioning
confidence: 99%
“…[1][2][3][4][5] In our previous articles on chemical modifications of linezolid, we reported synthesis and antibacterial activity of new structural isomers of oxazolidin-2-ones as a general structure (A) 3) or a bioisosteric replacement 6) of the oxazolidinone ring in linezolid 7) by a hydantoin nucleus (B) (Fig. 1).…”
mentioning
confidence: 99%